Three warm Jupiters orbiting TOI-6628, TOI-3837, and TOI-5027 and one sub-Saturn orbiting TOI-2328 - Tala, Marcelo; Jordán, Andrés; Acuña, Lorena; Jones, Matías; Brahm, Rafael; Reinarz, Yared; Eberhardt, Jan; Espinoza, Néstor; Henning, Thomas; Hobson, Melissa; Rojas, Felipe; Schlecker, Martin; et al. (Astronomy and astrophysics, 2025)
We report the discovery and characterization of three new transiting giant planets orbiting TOI-6628, TOI-3837, and TOI-5027 and one new warm sub-Saturn orbiting TOI-2328, whose transits events were detected in the light curves of the Transiting Exoplanet Survey Satell(TESS) space mission. By combining TESS light curves with ground-based photometric and spectroscopic follow-up observations, we confirm the planetary nature of the observed transits and radial velocity variations. TOI-6628 b has a mass of 0.74±0.06 MJ and a radius of 0.98+0.06 −0.05 RJ and orbits a metal-rich star with a period of 18.18424±0.00001 days and an eccentricity of 0.670+0.015 −0.016, making it one of the most eccentric orbits of all known warm giants. TOI-3837 b has a mass of 0.59±0.05 MJ and a radius of 0.97+0.05 −0.06 RJ and orbits its host star every 11.88865±0.00003 days, with a moderate eccentricity of 0.221+0.042 −0.046. With a mass of 2.02±0.13 MJ and a radius of 0.96+0.05 −0.06 RJ , TOI-5027 b orbits its host star in an eccentric orbit with e = 0.385+0.025 −0.026 every 10.24368±0.00001 days. TOI-2328 b is a Saturn-like planet with a mass of 0.16±0.02 MJ and a radius of 0.89+0.04 −0.05 RJ ; it orbits its host star in a nearly circular orbit with e = 0.057+0.046 −0.029 at a period of 17.10197±0.00001 days. All four planets have orbital periods above ten days, and our planet’s interior structure models are consistent with a rocky-icy core with an H/He envelope, providing evidence supporting the core-accretion model of planet formation for this kind of planet.
Online veröffentlicht am 19. Februar 2025
Gesehen am 02.12.2025